Smart Mobility Governance in Surabaya: Digital Innovation, Accessibility, and Sustainable Urban Transport - Deby Febriyan Eprilianto; Yuyun Eka Kartika Sari; Galih Wahyu Pradana; Adam Jamal; Revienda Anita Fitrie; Rianda Usmi (FOUNDAE (Foundation of Advanced Education), 2026)
Smart Mobility research often emphasizes digital applications, intelligent transport systems, or low-emission vehicles, but less attention has been given to how accessibility, environmental sustainability, and ICT integration are governed as interdependent public service dimensions in developing-country cities. This study addresses that gap by analyzing Smart Mobility governance in Surabaya, Indonesia, where Suroboyo Bus, Trans Semanggi, Feeder Wara-Wiri, the GOBIS application, cashless payments, and electric buses are being developed within one urban mobility system. Using a qualitative case study design, data were collected through field observation, semi-structured interviews, documentation, and literature-based conceptual review. Informants were selected through purposive sampling and consisted of 15 participants, including local government or transport authority representatives, public transport service personnel, passengers, and users representing accessibility or digital inclusion concerns. Thematic analysis supported by NVivo 15 was used to code and compare patterns related to accessibility, sustainability, ICT integration, and inclusion barriers. The findings show that Surabaya has improved mobility access through route information, bus stops, pedestrian facilities, passenger assistance, and digital travel information, but access remains uneven for wheelchair users, elderly passengers, and residents with weak first-mile and last-mile connections. Electric buses indicate potential operational emission reduction, although their long-term environmental benefit depends on the electricity mix, fleet scale, life-cycle impacts, and modal shift from private vehicles. GOBIS and cashless payments improve service transparency, journey planning, and user convenience, yet digital literacy, internet access, and application reliability remain critical barriers. The study contributes to Smart Mobility and smart governance literature by conceptualizing mobility innovation as an integrated governance process that must align digital systems, inclusive design, low-emission transport policy, and citizen-oriented service delivery.